ИККИ ТИЛЛИЛИК ШАРОИТИДА ЛЕКСЕМА ҲОСИЛ ҚИЛИШНИНГ БИР УСУЛИ ҲАҚИДА - Жўраев, Ш. (SCIENCE and SOCIETY, 2016)
The article tells about the word-changing in the Uzbek and Tajik languages of Zarafshan valley. As one of the specific peculiarities of word-changing in the two languages the morphological method is analyzed in accordance with materials. They are deeply revealed by using materials of formal, literary and conversational styles.
Keywords: Zarafshan valley; word-changing; morphological method; lexemes; bilingualism; lexsical system